Systems Skills … From Here to Diversity. Issue 3 (10th October 2022) - Harding, Alan
ABSTRACT: Competency, the ability to do things, is at the heart of how systems engineers realise successful systems. Over the years INCOSE and partners have codified what this means, initially in the INCOSE UK Competency Framework (INCOSE UK 2010) later adopted globally by INCOSE and used as the basis of the INCOSE Systems Engineering Competency Framework (INCOSE 2018) which, notably, included a new area of professional skills. This article considers competency from the perspective of Diversity, Equity, and Inclusion (referred to as DEI) using a variety of sources including the recently published INCOSE SE Vision 2035 (INCOSE 2022) and a variety of competency frameworks to offer a view of how the skills and competencies of systems engineers need to evolve in the future. Five new competencies are proposed, as are opportunities to improve the definitions of five more.